Expression of the Calcitonin Receptor-like Receptor (CALCRL) in Normal and Neoplastic Tissues - Wende, Benjamin; Beyer, Anna-Sophia Liselott; Ruhnke, Niklas; Kaemmerer, Daniel; Sänger, Jörg; Schulz, Stefan; Lupp, Amelie (International journal of molecular sciences, 2023)
Little information is available concerning protein expression of the calcitonin receptor-like receptor (CALCRL) at the protein level. Here, we developed a rabbit monoclonal antibody, 8H9L8, which is directed against human CALCRL but cross-reacts with the rat and mouse forms of the receptor. We confirmed antibody specificity via Western blot analyses and immunocytochemistry using the CALCRL-expressing neuroendocrine tumour cell line BON-1 and a CALCRL-specific small interfering RNA (siRNA). We then used the antibody for immunohistochemical analyses of various formalin-fixed, paraffin-embedded specimens of normal and neoplastic tissues. In nearly all tissue specimens examined, CALCRL expression was detected in the capillary endothelium, smooth muscles of the arterioles and arteries, and immune cells. Analyses of normal human, rat, and mouse tissues revealed that CALCRL was primarily present in distinct cell populations in the cerebral cortex; pituitary; dorsal root ganglia; epithelia, muscles, and glands of the larger bronchi; intestinal mucosa (particularly in enteroendocrine cells); intestinal ganglia; exocrine and endocrine pancreas; arteries, capillaries, and glomerular capillary loops in the kidneys; the adrenals; Leydig cells in the testicles; and syncytiotrophoblasts in the placenta. In the neoplastic tissues, CALCRL was predominantly expressed in thyroid carcinomas, parathyroid adenomas, small-cell lung cancers, large-cell neuroendocrine carcinomas of the lung, pancreatic neuroendocrine neoplasms, renal clear-cell carcinomas, pheochromocytomas, lymphomas, and melanomas. In these tumours with strong expression of CALCRL, the receptor may represent a useful target structure for future therapies.